Entropy and exergetic metrics for three spool turbofan engine with the aid of design parameters - Aygun, Hakan; Turan, Onder (Pergamon-Elsevier Science Ltd, 2025)
With the development of aviation industry, gas turbine engines have kept pace with innovations retrofitted on their systems. Recently, on new generation civil aircraft, three-spool turbofan engines have started to be observed due to their higher efficiency compared to previous generation. In this context, parametric and thermodynamic analyses are performed for three spool turbofan engine (TSTE) by considering the effects of bypass ratio (BPR), ranging from 7 to 10 and combustor pressure ratio (CPR), varying from 0.9 to 0.98. According to parametric analysis, for constant airflow, net thrust of TSTE decreases from 345.63 kN to 288.89 kN due to increased BPR whereas it enhances from 301.4 kN to 308.2 kN with effect of elevated CPR. However, specific fuel consumption of TSTE favorably affects from both variables. Namely, BPR and CPR increase, it decreases from 9.64 g/kN.s to 8.39 g/kN.s and from 8.84 g/kN.s to 8.65 g/kN.s, respectively. As for entropy assessments, total entropy production of six turbomachinery components decreases from 56.45 kW/K and 41.87 kW/K due to higher BPR whereas it slightly increases from 45.2 kW/K to 46.39 kW/K with increment of CPR. Lastly, exergy efficiency of TSTE experiences enhancement from both variables. Namely, it changes from 34.03% to 39.11% owing to raised BPR and from 37.09% to 37.93% with increment of CPR. These outcomes underline that increasing BPR benefits lowering fuel consumption with sacrificing thrust performance whereas raising CPR has relatively less effect on fuel saving without performance loss. It is thought that this study helps in finding the optimum points for considered performance requirements.
Keywords: Three spool turbofan; Exergy analysis; Parametric cycle analysis; Bypass ratio